3D-printed Model and guide plate for accurate resection of advanced cutaneous squamous cell carcinomas - Jiang, Weiqian; Chen, Peng; Cui, Lei; Li, Li; Shao, Yan; Zhang, Dekang; Xu, Lin; Tao, Ran; Chen, Youbai; Han, Yan (Frontiers in Surgery, 2023)
Purpose Advanced cutaneous squamous cell carcinomas (cSCC) can have unclear borders, and simple expanded resection may not only destroy surrounding normal tissues unnecessarily, but can also leave residual tumor cells behind. In this article, we describe a new method for resection and evaluate its accuracy. Methods The magnetic resonance imaging (MRI) data of 12 patients with advanced cSCC were reconstructed to obtain three-dimensional (3D) tumor models and guide plates for surgeries. Thirty-eight patients with the same cSCC stage, who underwent expanded resection, were included. The distances between the upper, lower, left and right horizontal margins and tumor pathological boundaries were classified as “positive”, “close” (0–6 mm), “adequate” (6–12 mm) or “excessive” (>12 mm). The positive margin rate and margin distance were compared between the groups. Results The 3D tumor models of 12 patients were all successfully reconstructed. The positive rate of 48 surgical margins in the guide plate group was 2.1%, and the proportion of “adequate” margins was 70.8%. A total of 152 margins of 38 patients were included in the extended resection group, for which the positive rate was 13.8%; this was higher than that of the guide plate group (P = 0.045). The proportion of “adequate” margins was 27.6%, with group differences seen in the distance distribution (P < 0.01). Conclusions In surgical resection of advanced cSCC, compared with simple expanded resection, surgical planning using a 3D tumor model and guide plate can reduce the rate of horizontal surgical margins, and the probability of under- or over-resection. Clinical Trial Registration: http://www.chictr.org.cn, Identifier [No. ChiCTR2100050174].